Minimum Number of Edges whose Removal Gives a Planar Graph - Nakprasit, Keaitsuda; Ieosanurak, Weenakorn (KKU Science Journal, 2014)
Let Ce(G) be the minimum number of edges whose removal from a graph G gives a planar graph. We investigate Ce(G) for complete graphs and complete k-partite graphs.